Mn < 4 + > / Dy < 3 + > co-doped lanthanum gallium silicate fluorescent enamel coating material as well as preparation method and application thereof

The preparation of enamel coatings by co-doping gallium lanthanum silicate phosphor by Mn4+ and Dy3+ is solved, and the performance of phosphor for white LEDs is insufficient, and efficient energy transfer and mechanical strength improvement is achieved. It is suitable for applications under extreme conditions.

CN120535199APending Publication Date: 2025-08-26QILU UNIVERSITY OF TECHNOLOGY (SHANDONG ACADEMY OF SCIENCES)
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510731249.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-03
Publication Date
2025-08-26

AI Technical Summary

Technical Problem

The thermal stability, luminous efficiency and color rendering index performance of existing phosphors for white LEDs need to be improved, and traditional rare earth ion doping systems have problems of high costs and limited regulation.

Method used

Mn4+ and Dy3+ co-doped gallium lanthanum silicate (LGS) phosphor is used to prepare enamel coating materials through high-temperature sintering, and combined with enamel glaze, to achieve high-efficiency energy transfer between ions and enhance mechanical strength.

Benefits of technology

It improves the optical properties and mechanical strength of the phosphor, expands its application potential under extreme conditions, and is especially suitable for high temperature and high strength environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120535199A_ABST
    Figure CN120535199A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of fluorescent materials, and relates to a Mn < 4 + > / Dy < 3 + > co-doped lanthanum gallium silicate fluorescent enamel coating material as well as a preparation method and application thereof. The material comprises enamel glaze, a fluorescent material and water, the chemical formula of the fluorescent material is La < 2.88 > Dy < 0.12 > Ga < 5 > (1-x) Mn < 5x > SiO < 14 >, and the value of x is 0.01, 0.02, 0.03, 0.04 or 0.05. According to the material, energy transfer of a Dy < 3 + >-Mn < 4 + > system in a sample is achieved, Dy < 3 + > and Mn < 4 + > ions are used for co-doping, the material is applied to novel stainless steel identification, the advantages of Dy < 3 + > and Mn < 4 + > ions are combined, and application research of LGS-based fluorescent powder in the aspect of functionalized enamel coatings is expanded. The material identification has the double characteristics of high strength, corrosion resistance, oxidation resistance and optical functions, the enamel coating identification material prepared from the material can be used as an effective novel luminous identification, the mechanical property and the corrosion resistance and oxidation resistance of a stainless steel identification are enhanced, the identification is endowed with the luminous property, the service life of the identification is prolonged, and the service life of the identification is prolonged. And the application prospect of the identification under harsh conditions such as high temperature is widened.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of fluorescent materials and relates to a Mn 4+ / Dy 3+ Co-doped lanthanum gallium silicate fluorescent enamel coating material, preparation method and application. Background Art

[0002] Since people learned about and mastered the power of fire, lighting has become indispensable to human life. The invention of the incandescent lamp in the late 19th century ushered in the era of electric lighting, and lighting sources have since undergone multiple generations of development. White light LEDs, a type of semiconductor electronic device, have become a mainstream lighting product. As a core material in lighting sources, phosphors are one of the most important factors affecting the luminous quality of white light LEDs. Currently, the thermal stability, luminous efficiency, and color rendering index of white light LED phosphors need to be improved, making the development of high-performance, high-quality white light LED phosphors urgent.

[0003] Ion doping is an important means of regulating the performance of phosphors, and a series of high-performance fluorescent materials have been synthesized (Jiang Hongyi, et al. Sol-gel synthesis of Sr2MgSi2O7:Eu 2+ ,Dy 3+ Long afterglow luminescent materials, Journal of Wuhan University of Technology, 2005). Yang Yuguo et al. prepared a series of fluorescent materials using solid phase synthesis method (Yang Yuguo, et al. Dy 3+ →Eu 3+ energy transfer in SrLaGa3O7: Dy 3+ / Eu 3+ phosphors, ECS Journal of Solid StateScience and Technology, 2021; Yang Yuguo, et al. Luminescence properties ofSrLaGa3O7fluorescent powders doped with Er 3+ and Yb 3+ , Optical Materials.). Lanthanum gallium silicate crystals (La3Ga5SiO 14Langasite (LGS) is a trigonal crystal with a structure similar to quartz and belongs to the P321 non-centrosymmetric space group. It has stable thermophysical properties and a small thermal expansion coefficient. It has no phase transition from room temperature to the molten state, making it an ideal phosphor matrix. However, there are few reports on the doping of lanthanide ions and other luminescent ions in LGS as a phosphor matrix (Georgescu S, et al. Spectroscopic characteristics of langasite (La3Ga5SiO 14 ) and langatate (La3Ga 5.5 Ta 0.5 O 14 ) crystals doped with Eu 3+ [J].Optical Materials, 2008), the literature on ion dual doping and other phosphors is even more scarce, the synthesis of lanthanum gallium silicate based phosphors and the exploration of their fluorescence properties and applications are of great research and application value. 4+ The application of LGS-based red phosphors as luminescent centers has attracted attention (Lou Youxin, Preparation and photoluminescence study of rare-earth-free red emitting La3Ga5SiO 14 :Mn 4+ phosphors, Functional Materials Letters, 2024; You Hongpeng, a Mn 4+ Doped red luminescent materials, preparation methods and new lighting sources, 2014). The study found that the dual-doping system may be easier to achieve performance control, such as Mn 4+ and Dy 3+ In the co-doped system, Dy 3+ As a sensitizer, Mn 4+ Luminescent properties, forming Dy 3+ →Mn 4+ energy transfer system, which points out a new direction for the realization of efficient optical tuning (Kangrui Qiang, Dy 3+ ,Mn 4+ co-doped phosphors for synergistic luminescent dual-mode thermometer and high-resolution imaging, 2024). Mn 4+ / Dy 3+The development of co-doped high-performance phosphors has become a hot topic, providing a new path for the development of new light sources.

[0004] The present invention uses Mn 4+ and Dy 3+ Co-doped in LGS matrix, Mn 4+ and Dy 3+ The synergistic effect of the LGS phosphors gives the LGS matrix the advantages of a wide spectral response and efficient red light emission, making it particularly suitable for cold white light control. The LGS phosphors exhibit excellent optical properties, effectively improving the material's energy transfer efficiency and the matrix's luminescence performance, overcoming the limitations of traditional rare earth doping systems. Simultaneously, the particles reduce the amount of Eu rare earth ions used, effectively reducing costs. Furthermore, the particles enhance the mechanical properties of enamel coatings (Chen Minghui, Research on the Mechanism of Particle Enhancement to Improve the Thermal Shock Resistance of Enamel Coatings, 2011). The chemically stable enamel coating structure also acts as a physical barrier, enhancing the corrosion resistance of stainless steel signs (Hu Yidong, Preparation and Performance Research of Highly Corrosion-Resistant Enamel Composite Coatings, 2018). To this end, LGS phosphors are combined with enamel frits and prepared through high-temperature sintering to create enamel signs. This not only imparts luminescent properties but also significantly improves the strength of sign components. This enamel coating structure gives the sign material greater strength and heat resistance, giving it unique application potential in high-temperature and high-intensity environments, such as high-temperature operations and aerospace (Liu Lei, A method for preparing a gas-erosion-resistant thermal insulation enamel coating on cast iron surfaces, 2024; Yang Xiaodong, Study on the hot corrosion behavior of enamel coatings in molten MgCl2-NaCl-KCl at 600°C, 2024).

[0005] This invention innovatively combines LGS phosphor with enamel, giving the product unique optical and mechanical properties, successfully developing a new LGS matrix logo, and providing a feasible path for the development and application of functional logo accessories. 4+ With Dy 3+ Co-doping not only achieves efficient energy transfer between ions, but also enhances the mechanical strength of the product, giving the new logo excellent luminescence characteristics and outstanding mechanical properties. It provides a theoretical basis and technical reserves for the design of future multifunctional logos and high-performance composite materials, and is particularly suitable for applications under extreme conditions, showing broad application prospects. Summary of the Invention

[0006] The present invention provides a Mn 4+ / Dy 3+ Co-doped lanthanum gallium silicate fluorescent enamel coating material and preparation method and application. 4+ 、Dy 3+ LGS-based phosphors were prepared using a co-doped system, and the fluorescent materials had high structural stability and luminescence tunability.

[0007] To achieve the above object, the present invention adopts the following scheme: A Mn 4+ / Dy 3+ The co-doped lanthanum gallium silicate fluorescent enamel coating material comprises solid powder and water, wherein the mass fraction of the solid powder is 35-60%; the solid powder comprises 60-95wt.% of enamel frit and 5-40wt.% of fluorescent material; the chemical formula of the fluorescent material is La 2.88 Dy 0.12 Ga 5(1-x) Mn 5x SiO 14 , the value of x is 0.01, 0.02, 0.03, 0.04, or 0.05.

[0008] The Mn 4+ / Dy 3+ The preparation method of the co-doped lanthanum gallium silicate fluorescent enamel coating material comprises the following specific steps: (1) Accurately weigh the corresponding molar amount of raw materials according to the stoichiometric ratio, add anhydrous ethanol to the raw materials, grind and mix, and then dry. The dried sample is cooled to room temperature in the furnace; (2) A portion of the cooled sample is compressed into tablets, and the other portion is used as embedding powder; (3) Embed the compressed sample with embedding powder; Then, the temperature is raised to a fixed temperature at a certain heating rate in an air atmosphere, kept at this temperature for a period of time, and then cooled at a certain cooling rate. After cooling with the furnace, the sample is allowed to stand and cooled to room temperature. The sample is in a block shape. After being taken out, it is ground and sieved to obtain Mn 4+ / Dy 3+ Co-doped lanthanum gallium silicate phosphor; (4) Place the glaze in a mortar, add ultrapure water, and grind until it becomes a slurry; then add Mn 4+ / Dy 3+ Co-doped lanthanum gallium silicate phosphor powder is fully mixed to obtain the Mn 4+ / Dy 3+ Co-doped lanthanum gallium silicate fluorescent enamel coating material.

[0009] Preferably, in step (1), an electronic balance is used to accurately weigh 0.00423 mol of La2O3, 0.00735(1-x) mol of Ga2O3, 0.000353 mol of Dy(CH3COO)3·yH2O, 0.0147x mol of MnO2, and 0.00294 mol of SiO2, where the value of x is 0.01, 0.02, 0.03, 0.04, and 0.05.

[0010] Preferably, the grinding time in step (1) is 30 to 60 min.

[0011] Preferably, in step (1), the drying temperature is 80-100° C., and the drying time is 150-250 min.

[0012] Preferably, the thickness of the tablet in step (2) is 3-7 mm.

[0013] Preferably, in step (3), the heating rate is 5-10°C / min, the heating temperature is 1200-1400°C, the holding time is 2-5 h, the cooling rate is 3-8°C / min, and the cooling temperature is 600-200°C.

[0014] Preferably, the glaze content in the slurry glaze in step (4) is 30-65 wt.%.

[0015] Preferably, in step (4), Mn 4+ / Dy 3+ Mn in co-doped lanthanum gallium silicate fluorescent enamel coating materials 4+ / Dy 3+ The mass fraction of the co-doped lanthanum gallium silicate phosphor is 5~40 wt.%.

[0016] The Mn 4+ / Dy 3+ The application of the co-doped lanthanum gallium silicate fluorescent enamel coating material is used for the preparation of enamel products. The application method includes the following steps: (1) The stainless steel substrate is first ultrasonically cleaned with acetone; then rinsed with deionized water, and then immersed in glacial acetic acid solution for pickling; the sample after pickling is ultrasonically cleaned in anhydrous ethanol, and dried to obtain a stainless steel sheet sample for later use; (2) The Mn 4+ / Dy 3+ The co-doped lanthanum gallium silicate fluorescent enamel coating material was applied on a stainless steel sample, dried naturally for a period of time, and then dried in a drying oven at 40-60°C. (3) The dried stainless steel sheet sample is first heated at a rate of 5-15°C / min, and then sintered at 700-850°C to obtain an enamel-coated product.

[0017] Preferably, the acetone ultrasonic cleaning time in step (1) is 5 to 30 minutes.

[0018] Preferably, the soaking time in step (1) is 5 to 24 hours.

[0019] Preferably, the ultrasonic cleaning time of anhydrous ethanol in step (1) is 5 to 30 minutes.

[0020] Preferably, the drying time in the drying oven in step (2) is 5 to 30 minutes.

[0021] Preferably, the sintering time in step (3) is 2 to 30 minutes.

[0022] Compared with the prior art, the Mn 4+ / Dy 3+ Co-doped lanthanum gallium silicate fluorescent enamel coating material has the following advantages: (1) Mn prepared by the above method 4+ / Dy 3+ Co-doped lanthanum gallium silicate fluorescent enamel coating material achieves Dy 3+ →Mn 4+ Energy transfer of the system, using Dy 3+ , Mn 4+ Ion co-doping combines the advantages of both and expands the application research of LGS-based phosphors in functional enamel coatings.

[0023] (2) Enamel has good wear resistance and high temperature resistance, and Mn 4+ / Dy 3+ Co-doped lanthanum gallium silicate (LGS) fluorescent material, a novel fluorescent material, exhibits excellent fluorescence properties. The resulting enamel-coated products were subjected to flexural strength and acid resistance tests. The combined materials demonstrated a 13.2-fold increase in flexural strength compared to uncoated samples. In an acidic solution, the enamel-coated marking exhibited approximately one-third the corrosion rate of the uncoated marking after 6 hours, significantly improving acid corrosion resistance. The combination of the two components imparts both high-strength structural strength and optical functionality to the marking.

[0024] (3) The present invention provides an effective luminous sign, enhances the mechanical properties and wear resistance of the enamel sign, gives the sign luminous properties, extends the service life of the sign, and broadens the application prospects of the sign under harsh conditions such as high temperature. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 This is the SEM image of the sample surface micromorphology of Example 1; Figure 2 The XRD pattern of the sample surface in Example 2; Figure 3 (a) Excitation spectrum and (b) emission spectrum analysis diagram of the sample of Example 3; Figure 4 is a fluorescence lifetime curve of the sample of Example 4; Figure 5 The CIE color coordinate diagram of the sample of Example 4; Figure 6 The luminescent marking sample of Example 4; Figure 7 This is a luminescent marking sample after high-temperature oxidation treatment. DETAILED DESCRIPTION

[0026] The present invention will be further described below in conjunction with specific embodiments, and the advantages and features of the present invention will become clearer as the description proceeds. However, the embodiments are merely exemplary and do not limit the scope of the present invention in any way. It should be understood by those skilled in the art that the details and forms of the technical solutions of the present invention may be modified or replaced without departing from the spirit and scope of the present invention, and such modifications and replacements fall within the scope of protection of the present invention.

[0027] Example 1 A Mn 4+ / Dy 3+ The preparation method of the co-doped lanthanum gallium silicate fluorescent enamel coating material comprises the following steps: (1) According to La 2.88 Dy 0.12 Ga 5(1-x) Mn 5x SiO 14 (x is taken as 0.01) stoichiometric ratio, use an electronic balance to accurately weigh 0.00423 mol of La2O3, 0.00735(1-x) mol of Ga2O3, 0.000353 mol of Dy(CH3COO)3·yH2O, 0.0147x mol of MnO2, and 0.00294 mol of SiO2; transfer the weighed raw materials to an agate mortar, add an appropriate amount of anhydrous ethanol, and grind for 30 min. After the raw materials are ground and mixed evenly, they are transferred to a beaker and placed in a dryer for drying at 100°C for 200 min. The dried sample is cooled to room temperature in the furnace and recorded as sample A. (2) The cooled sample A is then taken out and pressed into a tablet with a thickness of 5 mm using a tablet press. An appropriate amount of sample A mother powder is reserved and spread on the bottom of the corundum crucible. The pressed sample A is then placed in the crucible, and the remaining sample A mother powder is finally covered on the surface of the tablet for embedding.

[0028] (3) The crucible containing sample A was placed in a high-temperature box furnace, heated to 1400°C at a rate of 5°C / min in an air atmosphere, kept at this temperature for 3 h, and then cooled to 600°C at a rate of 5°C / min. The crucible was then taken out after cooling to below 200°C. The sample was cooled to room temperature and was in block form. After being taken out, it was ground and passed through a 300-mesh sieve to obtain Mn 4+ / Dy 3+ Co-doped lanthanum gallium silicate phosphor samples, such as Figure 1The SEM image in the middle shows uniform distribution of particles on the sample surface, with a relatively regular morphology, indicating no significant particle agglomeration or abnormally rapid grain growth during grain growth. The particles are stacked in an orderly manner along their respective crystal planes, resulting in similar particle sizes. This microstructural morphology demonstrates that the material's growth mechanism conforms to the layered growth theory.

[0029] (4) Place the glaze in a mortar and add ultrapure water, with the mass ratio of glaze to ultrapure water being 1:1, and continue grinding until the sample becomes a slurry; Then add 10 wt.% of Mn in step (3) to the slurry glaze. 4+ / Dy 3+ Co-doped lanthanum gallium silicate phosphor samples were mixed thoroughly to obtain Mn 4+ / Dy 3+ Co-doped lanthanum gallium silicate fluorescent enamel coating material.

[0030] Enamel coating product and preparation process Here are the steps: ① The above Mn 4+ / Dy 3+ The co-doped lanthanum gallium silicate fluorescent enamel coating material was coated on a stainless steel substrate with a size of 20×50×0.3 mm to obtain sample B. Sample B was placed in a drying oven at 50°C for 15 minutes. The substrate was pretreated in the following steps: S1: Place the substrate in a beaker, add acetone solvent into the beaker, and ultrasonically clean it for 5 min; S2: The substrate after acetone cleaning was rinsed with deionized water and then immersed in glacial acetic acid solvent for 5 h; S3: The acid-washed substrate obtained in S2 is ultrasonically cleaned in anhydrous ethanol for 5 minutes and dried for later use. This method is wet enameling, which can make the sample coating uniform and smooth. ② Place the dried sample B in a resistance furnace, heat it to 750°C at a rate of 10°C / min, and sinter it at 750°C for 30 min to obtain an enamel product.

[0031] Example 2 A Mn 4+ / Dy 3+ The preparation method of the co-doped lanthanum gallium silicate fluorescent enamel coating material comprises the following steps: (1) According to La 2.88 Dy 0.12 Ga 5(1-x) Mn 5x SiO 14Using an electronic balance, accurately weigh 0.00423 mol of La₂O₃, 0.00735(1-x) mol of Ga₂O₃, 0.000353 mol of Dy(CH₃COO)₃·yH₂O, 0.0147x mol of MnO₂, and 0.00294 mol of SiO₂ (x values ​​are 0.01, 0.02, 0.03, 0.04, and 0.05) in stoichiometric ratios. Transfer the weighed materials to an agate mortar and pestle, add an appropriate amount of anhydrous ethanol, and grind for 60 minutes. Once the materials are thoroughly ground and mixed, transfer them to a beaker and dry them in a drying oven at 80°C for 250 minutes. Cool the dried sample to room temperature and record it as Sample A. (2) Then take out the cooled sample A and use a tablet press to press the tablet to a thickness of 5 mm; and reserve an appropriate amount of sample A mother powder to spread on the bottom of the corundum crucible; then put the pressed sample A into the crucible, and finally cover the remaining sample A mother powder on the surface of the tablet for embedding.

[0032] (3) The crucible containing sample A was placed in a high-temperature box furnace, heated to 1300°C at a rate of 10°C / min in an air atmosphere, kept at this temperature for 4 h, and then cooled to 400°C at a rate of 5°C / min. The crucible was then taken out after cooling to below 200°C. The sample cooled to room temperature was sintered into a block, which was then taken out and ground and passed through a 300-mesh sieve to obtain Mn 4+ / Dy 3+ Co-doped lanthanum gallium silicate phosphor sample. Figure 2 The XRD pattern of the sample shows that Dy 3+ ,Mn 4+ The ions were successfully incorporated into the LGS matrix lattice without changing its crystal structure. 3+ ,Mn 4+ Ion substitution of La in LGS 3+ ion sites, and as Mn 4+ As the ion doping amount increases, the LGS lattice size decreases, and the degree of crystal structure change is related to the doping amount.

[0033] (4) Place the glaze in a mortar and add ultrapure water. The mass ratio of glaze to ultrapure water is 40:60. Grind until the sample becomes a slurry. Then add 5 wt.% of Mn in step (3) to the slurry glaze. 4+ / Dy 3+ Co-doped lanthanum gallium silicate phosphor samples were mixed thoroughly to obtain Mn 4+ / Dy 3+ Co-doped lanthanum gallium silicate fluorescent enamel coating material.

[0034] Enamel coating product and preparation process Here are the steps: ① The above Mn 4+ / Dy 3+ The co-doped lanthanum gallium silicate fluorescent enamel coating material was coated on a stainless steel substrate with a size of 20×50×0.3 mm to obtain sample B. Sample B was placed in a drying oven at 50°C and dried for 20 min. The substrate was pretreated in the following steps: S1: Place the substrate in a beaker, add acetone solvent into the beaker, and ultrasonically clean it for 5 min; S2: The substrate after acetone cleaning was rinsed with deionized water and then immersed in glacial acetic acid solvent for 5 h; S3: The acid-washed substrate obtained in S2 is ultrasonically cleaned in anhydrous ethanol for 5 minutes and dried for later use. This method is wet enameling, which can make the sample coating uniform and smooth. ② Place the dried sample B in a resistance furnace, heat it to 820°C at a rate of 10°C / min, and sinter it at 820°C for 3 minutes to obtain an enamel product.

[0035] Example 3 A Mn 4+ / Dy 3+ The preparation method of the co-doped lanthanum gallium silicate fluorescent enamel coating material comprises the following steps: (1) According to La 2.88 Dy 0.12 Ga 5(1-x) Mn 5x SiO 14 (The value of x is 0.01, 0.02, 0.03, 0.04, 0.05) stoichiometric ratio, use an electronic balance to accurately weigh 0.00423 mol of La2O3, 0.00735(1-x) mol of Ga2O3, 0.000353 mol of Dy(CH3COO)3·yH2O, 0.0147x mol of MnO2, and 0.00294 mol of SiO2; transfer the weighed raw materials to an agate mortar, add an appropriate amount of anhydrous ethanol, and grind for 50 min. After the raw materials are ground and mixed evenly, they are transferred to a beaker and placed in a dryer to dry at 90°C for 240 min. The dried sample is cooled to room temperature in the furnace and recorded as sample A. (2) The cooled sample A is then taken out and pressed into a tablet with a thickness of 5 mm using a tablet press. An appropriate amount of sample A mother powder is reserved and spread on the bottom of the corundum crucible. The pressed sample A is then placed in the crucible, and finally part of the sample A mother powder is covered on the surface of the tablet for embedding.

[0036] (3) The crucible containing sample A was placed in a high-temperature box furnace, heated to 1200°C at a rate of 6°C / min in an air atmosphere, kept at this temperature for 4 h, and then cooled to 400°C at a rate of 7°C / min. The crucible was then taken out after cooling to below 200°C. The sample was cooled to room temperature and was in block form. After being taken out, it was ground and passed through a 300-mesh sieve to obtain Mn 4+ / Dy 3+ Co-doped lanthanum gallium silicate phosphor sample. Figure 3 and Figure 4 Fluorescence spectrum analysis found that within the range of 380nm~765nm, LGS:0.15Mn 4+ The luminescence spectrum of LGS:0.12Dy 3+ The excitation spectra of the samples overlap. This indicates that there is Dy 3+ →Mn 4+ The energy transfer promotes Eu 3+ ions, thereby changing the Dy 3+ ions and Mn 4+ The ion doping ratio tunes the luminescence properties.

[0037] (4) Place the glaze in a mortar and add ultrapure water, with the mass ratio of glaze to ultrapure water being 55:45, and continue grinding until the sample becomes a slurry; Then add 15 wt.% of Mn in step (3) to the slurry glaze. 4+ / Dy 3+ Co-doped lanthanum gallium silicate phosphor samples were mixed thoroughly to obtain Mn 4+ / Dy 3+ Co-doped lanthanum gallium silicate fluorescent enamel coating material.

[0038] Enamel product coating and preparation process Here are the steps: ① The above Mn 4+ / Dy 3+ The co-doped lanthanum gallium silicate fluorescent enamel coating material was coated on a stainless steel substrate with a size of 20×50×0.3 mm to obtain sample B. Sample B was placed in a drying oven at 40°C and dried for 30 min. The substrate was pretreated in the following steps: S1: Place the substrate in a beaker, add acetone solvent into the beaker, and ultrasonically clean it for 5 min; S2: The substrate after acetone cleaning was rinsed with deionized water and then immersed in glacial acetic acid solvent for 5 h; S3: The acid-washed substrate obtained in S2 is ultrasonically cleaned in anhydrous ethanol for 5 minutes and dried for later use. This method is wet enameling, which can make the sample coating uniform and smooth. ② Place the dried sample B in a resistance furnace, heat it to 760°C at a rate of 10°C / min, and sinter it at 760°C for 15 minutes to obtain an enamel product.

[0039] Example 4 A Mn 4+ / Dy 3+ The preparation method of the co-doped lanthanum gallium silicate fluorescent enamel coating material comprises the following steps: (1) According to La 2.88 Dy 0.12 Ga 5(1-x) Mn 5x SiO 14 Using an electronic balance, accurately weigh 0.00423 mol of La₂O₃, 0.00735(1-x) mol of Ga₂O₃, 0.000353 mol of Dy(CH₃COO)₃·yH₂O, 0.0147x mol of MnO₂, and 0.00294 mol of SiO₂ (x = 0.02) in a stoichiometric ratio. Transfer the weighed materials to an agate mortar and pestle, add an appropriate amount of anhydrous ethanol, and grind for 40 minutes. Once the materials are thoroughly ground and mixed, transfer them to a beaker and dry them in a dryer at 90°C for 210 minutes. Cool the dried sample to room temperature and record it as Sample A. (2) Then take out the cooled sample A and press it into a tablet with a tablet press. The thickness of the tablet is 4 mm. A proper amount of sample A mother powder is reserved and spread on the bottom of the corundum crucible. Then put the pressed sample A into the crucible, and finally cover the surface of the tablet with the remaining sample A mother powder for embedding.

[0040] (3) The crucible containing sample A was placed in a high-temperature box furnace, heated to 1400°C at a rate of 9°C / min in an air atmosphere, kept at this temperature for 3 h, and then cooled to 500°C at a rate of 4°C / min. The crucible was then taken out after cooling to below 200°C. The sample was cooled to room temperature and then ground and passed through a 300-mesh sieve to obtain Mn 4+ / Dy 3+ Co-doped lanthanum gallium silicate phosphor sample. Figure 4 Fluorescence lifetime analysis showed that the sample had a long fluorescence lifetime.

[0041] (4) Place the glaze in a mortar and add ultrapure water. The mass ratio of glaze to ultrapure water is 60:40. Grind until the sample becomes a slurry. Then add 5 wt.% of Mn in step (3) to the slurry glaze. 4+ / Dy 3+ Co-doped lanthanum gallium silicate phosphor samples were mixed thoroughly to obtain Mn 4+ / Dy 3+Co-doped lanthanum gallium silicate fluorescent enamel coating material.

[0042] Enamel coating product and preparation process Here are the steps: ① The above Mn 4+ / Dy 3+ The co-doped lanthanum gallium silicate fluorescent enamel coating material was coated on a stainless steel substrate with a size of 20×50×0.3 mm to obtain sample B. Sample B was placed in a drying oven at 50°C and dried for 30 min. The substrate was pretreated in the following steps: S1: Place the substrate in a beaker, add acetone solvent into the beaker, and ultrasonically clean it for 5 min; S2: The substrate after acetone cleaning was rinsed with deionized water and then immersed in glacial acetic acid solvent for 5 h; S3: The acid-washed substrate obtained in S2 is ultrasonically cleaned in anhydrous ethanol for 5 minutes and dried for later use. This method is wet enameling, which can make the sample coating uniform and smooth. ② Place the dried sample B in a resistance furnace, heat it to 800°C at a rate of 10°C / min, and sinter it at 800°C for 5 minutes to obtain an enamel-coated product.

[0043] Comparative Example 1 Preparation process of enamel coating product The glaze was placed in a mortar and ultrapure water was added with a mass ratio of glaze to ultrapure water of 60:40. The sample was continuously ground until it became a slurry to obtain glaze slurry A. The glaze slurry A was directly applied to a stainless steel substrate with a size of 20×50×0.3 mm. The remaining steps were the same as the preparation process of the enamel product in Example 4.

[0044] Test Example 1 Sample luminescence performance evaluation The luminescence performance of the enamel samples obtained in Example 4 and Comparative Example 1 was tested. To characterize the luminescence color changes of the samples, the CIE color coordinates of the samples were plotted based on the spectra and expressed in the 1931-XYZ standard chromaticity diagram, as shown in FIG. Figure 5 Take the sample under the ultraviolet lamp of Example 4 as shown. Figure 6 As shown, the macroscopic surface of the marking after the coating is treated at 600℃ for 0.5-3h is as follows Figure 7 As shown in , it can be seen that the coating has good anti-oxidation effect.

Claims

1. A Mn 4+ / Dy 3+ Co-doped lanthanum gallium silicate fluorescent enamel coating material, characterized in that: Contains solid powder and water, wherein the mass fraction of the solid powder is 35-60%; the solid powder includes 60-95wt.% of enamel glaze and 5-40wt.% of fluorescent material; the chemical formula of the fluorescent material is La 2.88 Dy 0.12 Ga 5(1-x) Mn 5x SiO 14 , the value of x is 0.01, 0.02, 0.03, 0.04, or 0.

05.

2. Mn according to claim 1 4+ / Dy 3+ The preparation method of the co-doped lanthanum gallium silicate fluorescent enamel coating material is characterized in that: The following steps are involved: (1) Accurately weigh the corresponding molar amount of raw materials according to the stoichiometric ratio, add anhydrous ethanol to the raw materials, grind and mix, and then dry. The dried sample is cooled to room temperature in the furnace; (2) A portion of the cooled sample is compressed into tablets, and the other portion is used as embedding powder; (3) Embed the compressed sample with embedding powder; Then, the temperature was raised to a fixed temperature at a certain heating rate in an air atmosphere, kept at that temperature for a period of time, and then cooled at a certain cooling rate. After that, the temperature was cooled with the furnace, allowed to stand, and cooled to room temperature. The sample was in block shape, taken out, ground, and sieved to obtain Mn 4+ / Dy 3+ Co-doped lanthanum gallium silicate phosphor; (4) Place the glaze in a mortar, add ultrapure water, and grind until it becomes a slurry; then add Mn 4 + / Dy 3+ Co-doped lanthanum gallium silicate phosphor powder is fully mixed to obtain the Mn 4+ / Dy 3+ Co-doped lanthanum gallium silicate fluorescent enamel coating material.

3. Mn according to claim 2 4+ / Dy 3+ The preparation method of the co-doped lanthanum gallium silicate fluorescent enamel coating material is characterized in that: In step (1), an electronic balance is used to accurately weigh 0.00423 mol of La2O3, 0.00735(1-x) mol of Ga2O3, 0.000353 mol of Dy(CH3COO)3·yH2O, 0.0147x mol of MnO2, and 0.00294 mol of SiO2, where the values ​​of x are 0.01, 0.02, 0.03, 0.04, and 0.

05.

4. Mn according to claim 2 4+ / Dy 3+ The preparation method of the co-doped lanthanum gallium silicate fluorescent enamel coating material is characterized in that: The grinding time in step (1) is 30 to 60 min.

5. Mn according to claim 2 4+ / Dy 3+ The preparation method of the co-doped lanthanum gallium silicate fluorescent enamel coating material is characterized in that: In step (1), the drying temperature is 80-100°C and the drying time is 150-250 min.

6. Mn according to claim 2 4+ / Dy 3+ The preparation method of the co-doped lanthanum gallium silicate fluorescent enamel coating material is characterized in that: The thickness of the pressed tablet in step (2) is 3-7 mm.

7. Mn according to claim 2 4+ / Dy 3+ The preparation method of the co-doped lanthanum gallium silicate fluorescent enamel coating material is characterized in that: In step (3), the heating rate is 5-10°C / min, the heating temperature is 1200-1400°C, the holding time is 2-5 h, the cooling rate is 3-8°C / min, and the cooling temperature is 600-200°C.

8. Mn according to claim 2 4+ / Dy 3+ The preparation method of the co-doped lanthanum gallium silicate fluorescent enamel coating material is characterized in that: The glaze content in the slurry glaze in step (4) is 30-65 wt.%.

9. Mn according to claim 2 4+ / Dy 3+ The preparation method of the co-doped lanthanum gallium silicate fluorescent enamel coating material is characterized in that: Mn in step (4) 4+ / Dy 3+ Mn in co-doped lanthanum gallium silicate fluorescent enamel coating materials 4+ / Dy 3+ The mass fraction of the co-doped lanthanum gallium silicate phosphor is 5~40 wt.%.

10. Mn according to claim 1 4+ / Dy 3+ The application of the co-doped lanthanum gallium silicate fluorescent enamel coating material is characterized in that: For the preparation of enamel products, the application method includes the following steps: (1) The stainless steel substrate is first ultrasonically cleaned with acetone; then rinsed with deionized water, and then immersed in glacial acetic acid solution for pickling; the sample after pickling is ultrasonically cleaned in anhydrous ethanol, and dried to obtain a stainless steel sheet sample for later use; (2) The Mn 4+ / Dy 3+ The co-doped lanthanum gallium silicate fluorescent enamel coating material was applied on a stainless steel sample, dried naturally for a period of time, and then dried in a drying oven at 40-60°C. (3) The dried stainless steel sheet sample is first heated at a rate of 5-15°C / min, and then sintered at 700-850°C to obtain an enamel coating product; Preferably, the acetone ultrasonic cleaning time in step (1) is 5 to 30 minutes; Preferably, the soaking time in step (1) is 5 to 24 hours; Preferably, the ultrasonic cleaning time of anhydrous ethanol in step (1) is 5 to 30 min; Preferably, the drying time in the drying oven in step (2) is 5 to 30 minutes; Preferably, the sintering time in step (3) is 2 to 30 minutes.